Galectin-9 as an indicator of functional limitations and radiographic joint damage in patients with rheumatoid arthritis - Guo, Jiewen; Ai, Xiaoyuan; Jia, Baixue; Zhong, Xiaoling; Liu, Lixiong; Hu, Qiu; Xie, Jingyi; Hong, Xiaoping; Chen, Yulan; Liu, Dongzhou (Frontiers in Immunology, 2024)
Background: Previous studies have revealed that Galectin-9 (Gal-9) acts as an apoptosis modulator in autoimmunity and rheumatic inflammation. In the present study, we investigated the potential role of Gal-9 as a biomarker in patients with rheumatoid arthritis (RA), especially as an indicator of functional limitations and radiographic joint damage.Methods: A total of 146 patients with RA and 52 age-and sex-matched healthy controls were included in this study. Clinical data including disease activity, physical function, and radiographic progression were assessed. Serum Gal-9 levels were detected by an enzyme-linked immunosorbent assay (ELISA). Univariate and multivariate logistic regression analysis were used to evaluate the association between Gal-9 and high disease activity and functional limitations, and a prediction model was established to construct predictive nomograms.Results: Serum levels of Gal-9 were significantly increased in patients with RA compared to those in healthy controls (median 13.1 ng/mL vs. 7.6 ng/mL). Patients with RA who were older (>65 years), had a longer disease duration (>5 years), longer morning stiffness (>60mins), elevated serum erythrocyte sedimentation rate and Creactive protein, and difficult-to-treat RA had significantly higher Gal-9 levels than those in the corresponding control subgroups (all p <0.05). Patients with RA were divided into two subgroups according to the cut-off value of Gal-9 of 11.6 ng/mL.Patients with RA with Gal-9 >11.6 ng/mL had a significantly higher core clinical disease activity index, HAQ scores, Sharp/van der Heijde modified Sharp scores, as well as a higher percentage of advanced joint damage (all p<0.05) than patients with Gal-9 ≤11.6 ng/mL. Accordingly, patients with RA presenting either functional limitations or radiographic joint damage had significantly higher serum Gal-9 levels than those without (both p <0.05). Furthermore, multivariate logistic regression analysis showed that a serum level of Gal-9 >11.6 ng/mL was an independent risk factor for high disease activity (OR=3.138, 95% CI 1.150-8.567, p=0.026) and presence of functional limitations (OR=2.455, 95% CI 1.017-5.926, p=0.046), respectively.Conclusions: Gal-9 could be considered as a potential indicator in patients with RA, especially with respect to functional limitations and joint damage.